IMPLEMENTASI PERATURAN MENTERI PERDAGANGAN NOMOR 48/M-DAG/PER/7/2015 PASAL 2 AYAT (2)TERKAIT IMPOR BARANG BEKAS DI TEMBILAHAN - Muhammad Iqbal; Dessy Artina; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The attitude and behavior of people who prefer to buy imported used clothes because theyare tempted by foreign brands. Used clothing from abroad which includes goods prohibited fromimporting as regulated in the Regulation of the Minister of Trade Number 48/M-DAG/PER/7/2015.The entry of used clothes illegally imported into the domestic market has had a very bad impact onthe national economy as a whole. This is because the circulation of used clothes that are smuggledat a lower price will close the market for goods produced by domestic industries, which will resultin reduced stimulation or efforts to increase domestic production.This type of research can be classified in the type of sociological legal research (empirical),because in this study the author directly conducts research on the location or place under study inorder to provide a complete and clear picture of the problem being studied. This research wasconducted in the Tembilahan City Region, Indragiri Hilir Regency, Riau Province. The populationand samples are the Head of the Department of Trade and Industry of Indragiri Hilir Regency,Head of Trade Division of the Department of Trade and Industry of Indragiri Hilir Regency, Headof the Inspectorate General of Customs and Excise TMP C Tembilahan, Head of the Section forEnforcement and Investigation of Customs and Excise, Tembilahan Head of Health ResourcesDivision. Indragiri Hilir District Health, Secondhand Clothing Traders and the community. Sourcesof data used are primary data, and secondary data. Data collection techniques in this study wereinterviews, and literature review.The conclusions that can be obtained from the results of the research are First, theimplementation of Ministerial Regulation Number 48/M-Dag/Per/7/2015 Article 2 paragraph (2)related to the import of used goods in Tembilahan. This is what causes the used clothing business inTembilahan to still happen a lot. The sellers of used clothing there all know that what they areselling is actually not allowed to be traded and also the public's interest and dependence onimported used clothing does not make used clothing traders decrease, it just gets worse. increase.Second, the obstacles to implementing Ministerial Regulation Number 48/M-Dag/Per/7/2015Article 2 related to the import of used goods consist of Economic Factors, Inconsistency ofRegulations, and Limited resources, facilities and infrastructure. And Third, the government'sefforts in implementing the regulation of the minister of trade number 48/M-DAG/PER/7/2015article 2 paragraph 2 in Tembilahan is that it is necessary to develop a performance strategy forsocializing public understanding, supervision and also law enforcement so as to be able toovercome the implementation of Ministerial Regulation Number 48 /M-Dag/Per/7/2015 Article 2paragraph (2) regarding the import of used goods in TembilahanKeywords: Implementation, Regulation, Used Goods.